Manganese-based Prussian blue sodium-ion battery positive electrode material as well as preparation method and application thereof

Through ball mill solid phase synthesis method and post-treatment method, a micron-scale manganese-based Prussian blue sodium ion battery positive electrode material with low defects and low crystal water content was prepared, which solved the problems of capacity reduction and cycle performance deterioration in traditional synthesis methods, and achieved high discharge specific capacity and good cycle stability.

CN119706874APending Publication Date: 2025-03-28UNIV OF SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411916444.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Traditional sodium electropositive electrode materials are prone to crystallization water placeholding and ferrocyanium defects when synthesized in a water environment, resulting in reduced capacity and deterioration of circulation performance.

Method used

The ball mill solid phase synthesis method is adopted, and the positive electrode material of micron-scale manganese-based Prussian blue sodium ion battery with low defects and low crystallization water content is prepared by vacuum deoxygenation and sealing treatment, combined with post-treatment methods such as aging treatment, washing and drying.

Benefits of technology

It improves the discharge specific capacity and cycle stability of the positive electrode material, reduces the difficulty and cost of operation, and solves the defects caused by water environment synthesis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706874A_ABST
    Figure CN119706874A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of sodium-ion batteries, and particularly relates to a manganese-based Prussian blue sodium-ion battery positive electrode material as well as a preparation method and application thereof. The preparation method provided by the invention comprises the following steps: a) respectively carrying out ball milling and crushing on a manganese source, metal cyanate and an antioxidant to obtain nanoscale particles; b) transferring nanoscale manganese source particles, metal cyanate particles and antioxidant particles into a ball-milling tank, then carrying out vacuum deoxygenation and sealing treatment, and then carrying out ball-milling induced chemical reaction to carry out solid-phase synthesis; and c) carrying out aging treatment on the product obtained in the step b), and washing and drying the product after the aging treatment is finished to obtain the manganese-based Prussian blue sodium ion battery positive electrode material. According to the invention, a ball-milling solid-phase synthesis method is combined with an effective post-treatment means, so that the micron-sized manganese-based Prussian blue sodium-ion battery positive electrode material with low defect and low crystal water content is synthesized, and the positive electrode material has relatively high specific discharge capacity and relatively good cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of sodium ion batteries, and in particular relates to a manganese-based Prussian blue sodium ion battery positive electrode material and a preparation method and application thereof. Background Art

[0002] Carbon emissions caused by the increasing consumption of traditional non-renewable energy are an important reason for the imbalance of the global carbon cycle. The emergence of lithium-ion batteries has changed the traditional way of energy storage, and its research and development is an important way to build a clean and efficient energy system and achieve national goals. However, with the development of lithium-ion batteries, problems such as uneven distribution of lithium resources and relative shortage of resources have limited their application in large-scale energy storage systems. Under this situation, sodium-ion batteries are expected to become a strategic reserve of lithium-ion batteries with their advantages of low manufacturing cost and high safety, and the development of sodium-ion batteries has become a hot topic in the field of electrochemical energy storage research.

[0003] The cathode material is an important component of the battery system and is the key to determining the performance of sodium-ion batteries. The Prussian blue analogues in the traditional sodium cathode have an open framework structure, high theoretical specific capacity and a green and convenient synthesis process, and have been widely studied by many sodium researchers. Among them, the most studied are iron-based Prussian blue materials and manganese-based Prussian blue materials, and manganese-based Prussian blue has shown higher industrial application value with its higher charge and discharge potential. However, the water environment used in the commonly used co-precipitation synthesis method is very unfavorable to the performance of the cathode of Prussian blue analogues. In the synthesis, water will inevitably enter the crystal structure of the Prussian blue analogue, occupying the original sodium storage site, resulting in a decrease in capacity, and forming randomly distributed ferrocyanide defects, affecting the stability of the framework structure and causing the subsequent cycle performance to deteriorate rapidly. In contrast, the solid-phase synthesis method can eliminate the process of nucleation and growth of the material in a water environment, reduce the content of crystal water, and reduce the use of chelating agents and sodium supplements, reduce the residual impurities and reduce the cost of raw materials. However, solid-phase synthesis is based on the principle of mechanochemical synthesis, and the products obtained are nanoscale particles with low tap density and large specific surface area, which affects the coulombic efficiency and cycle stability of the positive electrode material and is not conducive to the energy density during full battery assembly. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a manganese-based Prussian blue-type sodium ion battery positive electrode material and a preparation method and application thereof. The present invention adopts a ball milling solid phase synthesis method with effective post-treatment means to synthesize a micron-level manganese-based Prussian blue-type sodium ion battery positive electrode material with low defects and low crystal water content. The sodium ion battery positive electrode material has a higher discharge specific capacity and better cycle stability.

[0005] The present invention provides a method for preparing a manganese-based Prussian blue sodium ion battery positive electrode material, comprising the following steps:

[0006] a) ball-milling a manganese source, a metal cyanate and an antioxidant to obtain nano-sized manganese source particles, nano-sized metal cyanate particles and nano-sized antioxidant particles;

[0007] b) transferring the nano-sized manganese source particles, nano-sized metal cyanate particles and nano-sized antioxidant particles into a ball mill, and adding ball mill beads; then vacuum deoxygenating and sealing the ball mill containing the materials, and then ball milling to induce a chemical reaction for solid phase synthesis;

[0008] c) placing the product obtained by ball milling in step b) in a vacuum or liquid medium for aging treatment; after the aging treatment, washing and drying the product to obtain a manganese-based Prussian blue sodium ion battery positive electrode material.

[0009] Preferably, in step a), the manganese source is at least one of manganese chloride, manganese oxalate, manganese sulfate, manganese nitrate, manganese acetate, manganese citrate and manganese acetylacetonate; the metal cyanate is at least one of sodium ferrocyanide, potassium ferrocyanide, sodium ferrocyanide and potassium ferrocyanide; and the antioxidant is at least one of ascorbic acid, tea polyphenols and ascorbyl palmitate.

[0010] Preferably, in step b), the amount of the nano-scale metal cyanate particles is 1 to 1.5 times the molar amount of the nano-scale manganese source particles; the amount of the nano-scale antioxidant particles is 1 to 20% of the total mass of the nano-scale manganese source particles and the nano-scale metal cyanate particles.

[0011] Preferably, in step b), the diameter of the ball milling beads is 1 to 5 mm; the amount of the ball milling beads is 8 to 15 times the total mass of the nano-scale manganese source particles, the nano-scale metal cyanate particles and the nano-scale antioxidant particles.

[0012] Preferably, in step b), before the vacuum deoxidation and sealing treatment, a solvent is added to the ball mill; the solvent is at least one of water, ice and liquid ethanol; the amount of the solvent is 0 to 45% of the total mass of the nanometer manganese source particles, nanometer metal cyanate particles and nanometer antioxidant particles.

[0013] Preferably, in step b), the ball milling speed for inducing the chemical reaction is 500 to 1200 rpm, and the ball milling time is 1 to 6 hours.

[0014] Preferably, in step b), before the ball milling to induce the chemical reaction, the material in the ball milling tank is ball milled and mixed; the rotation speed of the ball milling and mixing is 150 to 450 rpm, and the time is ≤12 hours.

[0015] Preferably, in step c), the liquid medium is water, polyvinyl pyrrolidone aqueous solution or ethanol; and the temperature of the aging treatment is 40-100°C.

[0016] The invention provides a manganese-based Prussian blue sodium ion battery positive electrode material, which is prepared according to the preparation method described in the above technical scheme.

[0017] The present invention provides a sodium ion battery, wherein the positive electrode material of the sodium ion battery comprises the manganese-based Prussian blue type sodium ion battery positive electrode material described in the above technical solution.

[0018] Compared with the prior art, the present invention provides a manganese-based Prussian blue type sodium ion battery positive electrode material and its preparation method and application. The preparation method provided by the present invention comprises the following steps: a) ball milling a manganese source, a metal cyanate and an antioxidant to obtain nano-scale manganese source particles, nano-scale metal cyanate particles and nano-scale antioxidant particles; b) transferring the nano-scale manganese source particles, nano-scale metal cyanate particles and nano-scale antioxidant particles to a ball milling jar, and adding ball milling beads; then vacuum deoxygenating and sealing the ball milling jar containing the materials, and then ball milling induces chemical reaction for solid phase synthesis; c) placing the product of step b) after ball milling in a vacuum or liquid medium for aging treatment; after the aging treatment is completed, washing and drying the product to obtain a manganese-based Prussian blue type sodium ion battery positive electrode material. The present invention adopts a ball milling solid phase synthesis method with effective post-treatment means to synthesize a micron-sized manganese-based Prussian blue sodium ion battery positive electrode material with low defects and low crystal water content. The sodium ion battery positive electrode material has a high discharge specific capacity and good cycle stability. More specifically, the preparation method of the present invention has the following beneficial effects:

[0019] (1) The manganese-based Prussian blue cathode material was synthesized by ball milling solid phase synthesis method, avoiding the water environment of co-precipitation synthesis. The obtained cathode material has low crystalline water content, few defects and high sodium content.

[0020] (2) The synthesis cycle of the ball milling solid-phase synthesis method is much shorter than that of the co-precipitation synthesis, which reduces the operation difficulty and time cost and is conducive to large-scale production.

[0021] (3) Unlike co-precipitation synthesis, which often requires the addition of chelating agents, sodium supplements and inert protective gases, the method of the present invention has a high raw material utilization rate, solves the problem of residual auxiliary raw materials in co-precipitation synthesis, saves production costs and sewage treatment costs, and is conducive to large-scale production.

[0022] (4) A green and simple post-processing method is adopted to increase the particle size of the product, thereby reducing the raw material cost and the difficulty of product separation.

[0023] (5) The manganese-based Prussian blue positive electrode material prepared by the present invention has a discharge specific capacity close to the theory, is stable in cycles during the charge and discharge process, and has excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0025] Figure 1 It is a scanning electron microscope photograph of the manganese-based Prussian blue positive electrode material prepared in Examples 1 to 3 provided by the present invention;

[0026] Figure 2 It is the X-ray diffraction spectrum of the pre-treated sample of the manganese-based Prussian blue positive electrode material prepared in Examples 1 to 3 provided by the present invention;

[0027] Figure 3 This is a charge-discharge curve diagram of the first week of the sodium positive electrode material prepared in Example 1 of the present invention at 0.1C;

[0028] Figure 4 This is a discharge capacity diagram of the sodium positive electrode material prepared in Example 1 provided by the present invention when cycled at 1C;

[0029] Figure 5 This is a discharge capacity diagram of the sodium positive electrode material prepared in Example 2 provided by the present invention when cycled at 1C;

[0030] Figure 6 This is a discharge capacity diagram of the sodium positive electrode material prepared in Example 3 provided by the present invention when cycled at 1C. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The present invention provides a method for preparing a manganese-based Prussian blue sodium ion battery positive electrode material, comprising the following steps:

[0033] a) ball-milling a manganese source, a metal cyanate and an antioxidant to achieve a high-activity state, thereby obtaining nano-sized manganese source particles, nano-sized metal cyanate particles and nano-sized antioxidant particles;

[0034] b) transferring the nano-sized manganese source particles, nano-sized metal cyanate particles and nano-sized antioxidant particles into a ball mill, and adding ball mill beads; then vacuum deoxygenating and sealing the ball mill containing the materials, and then performing solid phase synthesis by inducing chemical reaction through mechanical energy of ball milling;

[0035] c) placing the product obtained by ball milling in step b) in a vacuum or liquid medium for aging treatment; after the aging treatment, washing and drying the product to obtain a manganese-based Prussian blue sodium ion battery positive electrode material.

[0036] In the preparation method provided by the present invention, in step a), the manganese source is preferably at least one of hydrated or anhydrous manganese chloride, manganese oxalate, manganese sulfate, manganese nitrate, manganese acetate, manganese citrate and manganese acetylacetonate.

[0037] In the preparation method provided by the present invention, in step a), the metal cyanate is preferably at least one of hydrated or anhydrous sodium ferrocyanide, potassium ferrocyanide, sodium ferrocyanide and potassium ferrocyanide. In one embodiment provided by the present invention, the metal cyanate includes sodium cyanate and potassium cyanate, and the molar ratio of the sodium cyanate to the potassium cyanate is preferably (5-15):1, specifically 9:1.

[0038] In the preparation method provided by the present invention, in step a), the antioxidant is at least one of ascorbic acid, tea polyphenols and ascorbyl palmitate.

[0039] In the preparation method provided by the present invention, in step a), the rotation speed of the ball milling is preferably not less than 300 rpm, more preferably 300-800 rpm, specifically 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm or 800 rpm.

[0040] In the preparation method provided by the present invention, in step a), the particle sizes of the nanometer-sized manganese source particles, the nanometer-sized metal cyanate particles and the nanometer-sized antioxidant particles are independently preferably 10 to 500 nm, specifically 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm or 500 nm.

[0041] In the preparation method provided by the present invention, in step b), the amount of the nanoscale metal cyanate particles is preferably 1 to 1.5 times the molar amount of the nanoscale manganese source particles, specifically 1 time, 1.05 times, 1.06 times, 1.07 times, 1.1 times, 1.15 times, 1.2 times, 1.25 times, 1.3 times, 1.35 times, 1.4 times, 1.45 times or 1.5 times.

[0042] In the preparation method provided by the present invention, in step b), the amount of the nano-scale antioxidant particles preferably accounts for 1-20% of the total mass of the nano-scale manganese source particles and the nano-scale metal cyanate particles, and specifically can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.

[0043] In the preparation method provided by the present invention, in step b), the diameter of the ball milling beads is preferably 1 to 5 mm, specifically at least one of 1 mm, 2 mm, 3 mm and 5 mm ball milling beads. In one embodiment provided by the present invention, the ball milling beads are all 2 mm ball milling beads; in another embodiment provided by the present invention, the ball milling beads include 1 mm ball milling beads, 2 mm ball milling beads and 5 mm ball milling beads, and the mass ratio of the 1 mm ball milling beads, 2 mm ball milling beads and 5 mm ball milling beads is preferably (1 to 3): (1 to 3): 1, specifically 2: 2: 1; in other embodiments provided by the present invention, the ball milling beads include 3 mm ball milling beads and 5 mm ball milling beads, and the mass ratio of the 3 mm ball milling beads to the 5 mm ball milling beads is preferably (2 to 4): 1, specifically 3: 1.

[0044] In the preparation method provided by the present invention, in step b), the amount of the ball milling beads is preferably 8 to 15 times the total mass of the nanometer manganese source particles, the nanometer metal cyanate particles and the nanometer antioxidant particles, and specifically can be 8 times, 9 times, 10 times, 11 times, 12 times, 13 times, 14 times or 15 times.

[0045] In the preparation method provided by the present invention, in step b), before the vacuum deoxidation and sealing treatment, a solvent is preferably added to the ball mill; the solvent is preferably at least one of water, ice and liquid ethanol; the amount of the solvent is preferably 0 to 45% of the total mass of the nanometer manganese source particles, the nanometer metal cyanate particles and the nanometer antioxidant particles, and specifically can be 0, 1%, 3%, 5%, 7%, 10%, 12%, 15%, 17%, 20%, 23%, 25%, 27%, 30%, 32%, 35%, 37%, 40%, 42% or 45%.

[0046] In the preparation method provided by the present invention, in step b), the ball milling speed for inducing the chemical reaction by ball milling is preferably 500-1200rpm, specifically 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, 750rpm, 800rpm, 850rpm, 900rpm, 950rpm, 1000rpm, 1050rpm, 1100rpm, 1150rpm or 1200rpm; the ball milling time for inducing the chemical reaction by ball milling is preferably 1-6h, specifically 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 6h.

[0047] In the preparation method provided by the present invention, in step b), before the ball milling to induce the chemical reaction, the material in the ball mill jar is preferably ball milled and mixed; the rotation speed of the ball milling and mixing is 150-450rpm, specifically 150rpm, 1200rpm, 250rpm, 300rpm, 350rpm, 400rpm or 450rpm; the time of the ball milling and mixing is preferably ≤12h, specifically 0, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h.

[0048] In the preparation method provided by the present invention, in step c), the liquid medium is preferably water, polyvinyl pyrrolidone (PVP) aqueous solution or ethanol; the concentration of the polyvinyl pyrrolidone aqueous solution is preferably (0.5-10) g / 100 mL, specifically 0.5 g / 100 mL, 1 g / 100 mL, 1.5 g / 100 mL, 2 g / 100 mL, 3 g / 100 mL, 4 g / 100 mL, 5 g / 100 mL, 6 g / 100 mL, 7 g / 100 mL, 8 g / 100 mL, 9 g / 100 mL or 10 g / 100 mL.

[0049] In the preparation method provided by the present invention, in step c), the temperature of the aging treatment is preferably 40-100°C, specifically 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C; the time of the aging treatment is preferably 2-24h, specifically 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h.

[0050] In the preparation method provided by the present invention, in step c), the drying is preferably carried out under vacuum and / or protective gas atmosphere, and the protective gas is preferably nitrogen and / or argon; the drying temperature is preferably 60-250°C, specifically 60°C, 80°C, 100°C, 120°C, 150°C, 180°C, 200°C, 230°C or 250°C; the drying time is preferably 6-48h, specifically 6h, 12h, 18h, 24h, 30h, 36h, 42h or 48h.

[0051] The present invention also provides a manganese-based Prussian blue sodium ion battery positive electrode material, which is prepared according to the preparation method described in the above technical solution.

[0052] In the present invention, the molecular formula of the manganese-based Prussian blue sodium ion battery positive electrode material is preferably A a Mn[Fe(CN)6] 1-b H2O, wherein 1<a≤2, 0<b≤1, A is preferably Na and / or K.

[0053] In the present invention, the manganese-based Prussian blue sodium ion battery positive electrode material is nanometer or micrometer sized, and its particle size is preferably 50nm to 5μm.

[0054] The present invention also provides a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrode liquid and a separator, wherein the positive electrode material on the positive electrode sheet comprises the manganese-based Prussian blue sodium ion battery positive electrode material described in the above technical solution.

[0055] For the purpose of greater clarity, the invention is described in detail through the following examples.

[0056] Example 1

[0057] This example prepares a manganese-based Prussian blue sodium ion battery positive electrode material, and the specific process is as follows:

[0058] (1) Preparation of positive electrode

[0059] Manganese oxalate, sodium ferrocyanide and ascorbic acid were respectively crushed into 100 nm particles by high-energy ball milling to achieve a highly active state.

[0060] The above 30 mmol (4.3 g) of manganese oxalate, 32 mmol (15.5 g) of sodium ferrocyanide decahydrate and 6 mmol (1.05 g) of ascorbic acid were added to a ball mill, and then 180 g of zirconium oxide ball mill beads with a diameter of 2 mm were added, followed by 5 g of ice cubes made of deionized water.

[0061] The ball mill containing the material was quickly vacuum deoxygenated and sealed, and the material was first ball-milled at 300 rpm for 12 hours to mix the material evenly, and then ball-milled at 600 rpm for 3 hours. During the 600 rpm high-speed ball milling process, mechanical energy induced chemical reaction for solid phase synthesis.

[0062] After the reaction, the ball mill was directly placed in a vacuum oven at 60 °C for 4 h, and then deionized water was added to separate the sample and the ball mill beads, and the ball mill beads were removed through a sieve.

[0063] The sample after the ball milling beads were screened out was first washed 3 times with deionized water, then washed 2 times with anhydrous ethanol, centrifuged at 6000 rpm, and centrifuged for 3 min. The sample was then dried in a 60°C vacuum oven for 12 h to obtain a pre-treated sample, and then treated in a 150°C nitrogen-filled oven for 6 h to obtain a sample of Example 1 of a manganese-based Prussian blue sodium ion battery positive electrode material.

[0064] The above sample, conductive agent SuperP, and binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 8:1:1, and solvent N-methylpyrrolidone was added and stirred to obtain positive electrode slurry. Then, it was coated on a positive electrode current collector aluminum foil with a thickness of 15 μm, and then punched into a positive electrode sheet with a diameter of 12 mm after drying at 100 ° C. The positive electrode slurry was heated to a density of 2 mg / cm 2 .

[0065] (2) Preparation of negative electrode sheet

[0066] The negative electrode directly uses metallic sodium sheet.

[0067] (3) Preparation of electrolyte

[0068] In an argon atmosphere glove box (H2O<0.01ppm, O2<0.01ppm), fully dried sodium salt NaClO4 was dissolved in PC organic solvent, and 5% by mass FEC was added as an electrolyte additive to obtain an electrolyte in which the NaClO4 concentration was 1 mol / L.

[0069] (4) Preparation of isolation membrane

[0070] A glass fiber membrane (produced by Whatman) was used as an isolation membrane and punched into a disc with a diameter of 16 mm.

[0071] (5) Preparation of button batteries

[0072] Stack the positive electrode sheet, the separator, and the negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, inject the prepared electrolyte into the dry battery cell, and assemble it into a CR2032 button battery.

[0073] Example 2

[0074] The preparation process of the button cell is the same as that of Example 1, except that:

[0075] (1) Preparation of positive electrode

[0076] Manganese sulfate, sodium ferrocyanide, potassium ferrocyanide and tea polyphenols are respectively crushed into 100nm particles by high-energy ball milling to achieve a highly active state.

[0077] The above-mentioned 20 mmol (5.2 g) of manganese sulfate hexahydrate, 18 mmol (5.45 g) of sodium ferrocyanide, 2 mmol (0.74 g) of potassium ferrocyanide and 1 g of tea polyphenols were added to a ball mill, and 150 g of zirconium oxide ball mill beads with a diameter and a mass ratio of 1 mm: 2 mm: 5 mm = 40%: 40%: 20% were added, followed by 5 g of anhydrous ethanol.

[0078] The ball mill containing the material was quickly vacuum deoxygenated and sealed, and the material was first ball-milled at 450 rpm for 6 hours to mix the material evenly, and then ball-milled at 1000 rpm for 3 hours. During the 1000 rpm high-speed ball milling process, mechanical energy induced chemical reaction for solid phase synthesis.

[0079] After the reaction, the ball mill was directly placed in a vacuum oven at 80 °C for 4 h, and then deionized water was added to separate the sample and the ball mill beads, and the ball mill beads were removed through a sieve.

[0080] The sample after the ball milling beads were removed was first washed 3 times with deionized water, then washed 2 times with anhydrous ethanol, centrifuged at 6000 rpm for 3 min, and then dried in a 60°C vacuum oven for 12 h to obtain a pre-treated sample, and then treated in a 180°C nitrogen-filled oven for 6 h to obtain a manganese-based Prussian blue sodium ion battery positive electrode material Example 2 sample.

[0081] Example 3

[0082] The preparation process of the button cell is the same as that of Example 1, except that:

[0083] (1) Preparation of positive electrode

[0084] Manganese acetate, sodium ferrocyanide and ascorbic acid are respectively crushed into 50nm particles by high-energy ball milling to achieve a highly active state.

[0085] The above-mentioned 20 mmol manganese acetate tetrahydrate (4.9 g), 21 mmol sodium ferrocyanide (6.4 g) and 0.7 g ascorbic acid were added to a ball mill, and 150 g of zirconium oxide ball milling beads with a diameter and a mass ratio of 3 mm:5 mm = 75%:25% were added, followed by 3 g of deionized water.

[0086] The ball mill jar containing the material was quickly vacuum deoxygenated and sealed, and ball milled at 800 rpm for 6 hours. During the 800 rpm high-speed ball milling process, mechanical energy induced chemical reaction to perform solid phase synthesis.

[0087] After the reaction is completed, deionized water is added to separate the sample and the ball milling beads, and the ball milling beads are removed through a sieve. The sample after the ball milling beads are removed is placed in a flask and a protective gas is introduced, followed by a water bath at 60°C for 6 hours.

[0088] The sample that has completed water bath aging was first washed 3 times with deionized water, then washed 2 times with anhydrous ethanol, centrifuged at 6000 rpm, and centrifuged for 3 min. It was then dried in a 60°C vacuum oven for 12 h to obtain a pre-treated sample, and then treated in a 180°C nitrogen-filled oven for 12 h to obtain a manganese-based Prussian blue sodium ion battery positive electrode material Example 3 sample.

[0089] Effect evaluation

[0090] (1) Microscopic morphology characterization of cathode materials

[0091] The manganese-based Prussian blue sodium ion battery positive electrode material samples prepared in Examples 1 to 3 were observed by scanning electron microscopy. Figure 1 As shown, (a) is embodiment 1, (b) is embodiment 2, and (c) is embodiment 3. Figure 1 It can be seen that the sample is composed of secondary particles formed by the accumulation of square primary particles. The particle size of Example 1 is 50-400 nm, the particle size of Example 2 is 100-1 μm, and the particle size of Example 3 is 200 nm-2 μm.

[0092] (2) X-ray diffraction characterization of cathode materials

[0093] X-ray diffraction analysis was performed on the manganese-based Prussian blue sodium ion battery positive electrode material samples prepared in Examples 1 to 3. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the samples all exhibit a monoclinic phase with a high content of alkali metal elements, which is conducive to the capacity utilization in subsequent performance tests.

[0094] (3) Crystal water content test

[0095] Thermogravimetric testing was performed on the manganese-based Prussian blue sodium-ion battery positive electrode material samples prepared in Examples 1 to 3, and the results showed that the water content of the samples was 2 to 3%.

[0096] (4) Electrical performance of sodium ion batteries

[0097] The sodium ion button cells prepared in Examples 1 to 3 were subjected to charge-discharge and cycle performance tests. Figures 3 to 6 As shown in Table 1:

[0098] Example No. 0.1C Coulomb efficiency (%) <![CDATA[0.1C discharge specific capacity (mAh g -1 )]]> 1 93.1 166 2 96.1 137 3 83 160.4

[0099] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a manganese-based Prussian blue sodium ion battery positive electrode material, characterized in that: The following steps are involved: a) ball-milling a manganese source, a metal cyanate and an antioxidant to obtain nano-sized manganese source particles, nano-sized metal cyanate particles and nano-sized antioxidant particles; b) transferring the nano-sized manganese source particles, nano-sized metal cyanate particles and nano-sized antioxidant particles into a ball mill, and adding ball mill beads; then vacuum deoxygenating and sealing the ball mill containing the materials, and then ball milling to induce a chemical reaction for solid phase synthesis; c) placing the product obtained by ball milling in step b) in a vacuum or liquid medium for aging treatment; after the aging treatment, washing and drying the product to obtain a manganese-based Prussian blue sodium ion battery positive electrode material.

2. The preparation method according to claim 1, characterized in that: In step a), the manganese source is at least one of manganese chloride, manganese oxalate, manganese sulfate, manganese nitrate, manganese acetate, manganese citrate and manganese acetylacetonate; the metal cyanate is at least one of sodium ferrocyanide, potassium ferrocyanide, sodium ferrocyanide and potassium ferrocyanide; and the antioxidant is at least one of ascorbic acid, tea polyphenols and ascorbyl palmitate.

3. The preparation method according to claim 1, characterized in that: In step b), the amount of the nano-scale metal cyanate particles is 1 to 1.5 times the molar amount of the nano-scale manganese source particles; the amount of the nano-scale antioxidant particles is 1 to 20% of the total mass of the nano-scale manganese source particles and the nano-scale metal cyanate particles.

4. The preparation method according to claim 1, characterized in that: In step b), the diameter of the ball milling beads is 1 to 5 mm; the amount of the ball milling beads used is 8 to 15 times the total mass of the nano-scale manganese source particles, the nano-scale metal cyanate particles and the nano-scale antioxidant particles.

5. The preparation method according to claim 1, characterized in that: In step b), before the vacuum deoxidation and sealing treatment, a solvent is added to the ball mill; the solvent is at least one of water, ice and liquid ethanol; the amount of the solvent is 0 to 45% of the total mass of the nano-scale manganese source particles, the nano-scale metal cyanate particles and the nano-scale antioxidant particles.

6. The preparation method according to claim 1, characterized in that: In step b), the ball milling speed for inducing the chemical reaction is 500-1200 rpm, and the ball milling time is 1-6 hours.

7. The preparation method according to claim 1, characterized in that: In step b), before the ball milling to induce chemical reaction, the material in the ball milling tank is ball milled and mixed; the rotation speed of the ball milling and mixing is 150-450 rpm, and the time is ≤12h.

8. The preparation method according to claim 1, characterized in that: In step c), the liquid medium is water, polyvinyl pyrrolidone aqueous solution or ethanol; the temperature of the aging treatment is 40-100°C.

9. A manganese-based Prussian blue sodium ion battery positive electrode material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.

10. A sodium ion battery, characterized in that: The positive electrode material of the sodium ion battery includes the manganese-based Prussian blue sodium ion battery positive electrode material according to claim 9.